A facile precipitation procedure for synthesis of binary Sn-Co oxide promoting Pd catalyst towards glucose electrooxidation. (20th January 2016) - Chai, Dan; Wang, Wei; Wang, Fengxia; Kang, Yumao; Yang, Yan; Lei, Ziqiang
Graphical abstract: Highlights: Prepared Pd-SnCoOx /C catalyst via precipitation and polyol methods. Pd-SnCoOx /C catalyst shows high performance for glucose oxidation. Concluded synergistic effect between Sn-Co oxide and Pd nanoparticles. Investigated the effects of concentrations and scan rates. Abstract: To improve the electrocatalytic activity of Pd for glucose oxidation, a novel binary Sn-Co oxide promoting Pd catalyst (Pd-SnCoOx /C) is synthesized via facile precipitation and polyol methods. Electrochemical results show that Pd-SnCoOx /C exhibits excellent electrocatalytic performance for glucose oxidation. Compared with Pd/C catalyst, as-prepared Pd-SnCoOx /C catalyst has larger electrochemically active surface area, higher electrochemical activity and superior stability. The high catalytic performance may be attributed to the synergistic effect between binary Sn-Co oxide and Pd nanoparticles, leading to smaller size and higher dispersion for Pd-SnCoOx /C than Pd/C. To further understand the glucose oxidation, the tafel plots, effects of concentrations and scan rates are also investigated.